Social networks and psychological safety: A model of contagion - André Escórcio Soares; Miguel Pereira Lopes (Journal of Industrial Engineering and Management (JIEM), 2014)
Purpose: We attempted to explain how the interactions between members influence the psychological safety of a team using social network analysis by proposing a model based on social contagion in which the psychological safety of the central node has a key role in the psychological safety of the whole team. Design/methodology/approach: We present a theoretical paper which crosses theory about social network analysis, psychological safety and social contagion. Findings and Originality/value: We suggest that there are two groups of variables that mediate this relationship. The first group concerns the characteristics of the node and is composed by the proximity to the node's personal characteristics and the value of the central node as a source of information. Second, we advance that there are two dimensions at the level of tie properties that mediate the influence of a central node on team psychological safety - tie strength and friendship level. Finally, the interacting opportunities- a variable at context level - is considered to affect the strength of the ties. We also advance some variables that mediate the influence of the psychological safety of a central node on the psychological safety of the team. Originality/value: To the best of our knowledge there is no significant research using social network analysis to explain the process by which a team becomes psychologically safe. On the other hand, because psychological safety tends to be a team construct it is important to understand how team dynamics, evidenced by social network analysis, influence the formation of psychological safety through contagion processes.
Keywords: 650; Psychological safety; Teams; Social network analysis; Contagion